Pengaruh Kecerdasan Emosional, Perilaku Belajar Dan Cara Mengajar Dosen Terhadap Pemahaman Akuntansi Mahasiswa Di Masa Pandemi - Muna Wara; Herlina Pusparini; Adhitya Bayu Suryantara (Universitas Hamzanwadi, 2022)
This study aims to examine the effect of emotional intelligence, learning behavior and teaching methods of lecturers on accounting understanding during the Covid 19 pandemic. The study was conducted on undergraduate accounting students of 2017 and 2018 who had taken compulsory accounting courses. This type of research is an associative study which aims to determine the effect of emotional intelligence, learning behavior and teaching methods of lecturers on accounting understanding during the Covid 19 pandemic. Data processing techniques use multiple linear regression analysis method with IBM SPSS 26 software application. The results of this study indicate that emotional intelligence affects accounting understanding with a significant value of emotional intelligence during the Covid 19 pandemic, learning behavior does not affect accounting understanding during the Covid 19 pandemic, this is due to several factors such as poor study habits, namely poor study time. Regular and poor reading habits, especially during this pandemic, students study independently at home so that their learning behavior is irregular. The way of teaching lecturers has an effect on accounting understanding during the COVID-19 pandemic